2017
DOI: 10.4236/jacen.2017.61003
|View full text |Cite
|
Sign up to set email alerts
|

Review Paper: The Fundamentals of Biochar as a Soil Amendment Tool and Management in Agriculture Scope: An Overview for Farmers and Gardeners

Abstract: Improving the soil and biomass with coal is estimated at the international level as a way to enhance soil productiveness, fertility and also to mitigate climate change. Biochar employed to improve land scope and impound carbon, is attracting a great deal of attention. Its characteristics of chemical, physical and biological properties, containing big surface area, CEC (Cation Exchange Capacity), high water-holding capacity, size of pore, volume, distribution, and element composition, affect its recognized infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 93 publications
(63 reference statements)
1
16
0
1
Order By: Relevance
“…Many of the studies, including laboratory studies, concluded positive effects of biochar application on crop productivity (Jeffery et al, 2011;Zhang et al, 2012; GRAPHICAL ABSTRACT | Biochar application effects on soil amendment and crop yield. Biederman and Stanley, 2013;Shareef and Zhao, 2017). On the contrary, some studies in temperate regions have reported no effect or negative effects on crop productivity (Hussain et al, 2017;Sänger et al, 2017;Cornelissen et al, 2018;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the studies, including laboratory studies, concluded positive effects of biochar application on crop productivity (Jeffery et al, 2011;Zhang et al, 2012; GRAPHICAL ABSTRACT | Biochar application effects on soil amendment and crop yield. Biederman and Stanley, 2013;Shareef and Zhao, 2017). On the contrary, some studies in temperate regions have reported no effect or negative effects on crop productivity (Hussain et al, 2017;Sänger et al, 2017;Cornelissen et al, 2018;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its large surface area, porous structure and high mineral content, EB has been utilized as an air and water scrubber, as well as a soil amendment (2, 4). Improvements in crop yields and soil fertility (5) as well as decreases in nitrous oxide (N 2 O) and CH 4 from fields have been reported when biochar was included as a soil amendment (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar characteristics e.g., chemical composition, surface chemistry, particle and pore size distribution, physical and chemical stabilisation mechanisms in soils, determine its effects on soil functions [21]. Application of biochar to enhance soil quality, adaptation and mitigation of climate variability has been reported by many researchers [12,[22][23][24][25][26][27][28]. Biochar incorporation increases aggregate stability by acting as a binding agent the formation of macroaggregates [29,30].…”
Section: Introductionmentioning
confidence: 99%